High-load high-bonding pure alpha-ta coating and method for preparing same

CN118207505BActive Publication Date: 2026-10-16UNIV OF SCI & TECH BEIJING
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410243799.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-04
Publication Date
2026-10-16
Estimated Expiration
2044-03-04

AI Technical Summary

Technical Problem

[0003]目前的研究认为,获得α-Ta有如下途径:(1)使用Kr和Xe等重气体作为沉积的气氛(价格高昂);(2)使用较高的温度,如高于375℃的沉积温度(CN108103463B、CN101323946A)或在沉积后进行650℃以上的后热处理(CN116334542A)(即便是375℃,也会对轻合金如铝、镁等和低温回火的马氏体钢产生硬度下降等性能变差的影响,对部分钢材甚至会引起回火脆性);(3)去除基体表面吸附和固溶氧的影响,如先沉积一层Cr或者Ti用于隔绝基体表面与Ta涂层(产生额外的异质界面,存在由于弹性模量或热膨胀系数差异造成涂层分层甚至剥脱的潜在隐患)

Benefits of technology

[0031] (1) Multilayer alternating pure α-Ta design: By using a base layer of the same element as the coating to isolate the substrate from the coating body, more heterogeneous interfaces are avoided; at the same time, the base layer and the substrate surface have an in-situ raised and recessed interface, which can effectively enhance the film-substrate bonding force; the multilayer alternating design of the coating body with different properties can realize the control of coatings with different properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118207505B_ABST
    Figure CN118207505B_ABST
Patent Text Reader

Abstract

The application discloses a high-load high-bonding pure alpha-Ta coating and a preparation method thereof, and relates to the field of physical vapor deposition. The crystal structure of the coating is a single body-centered cubic lattice alpha phase, and the hardness is 550-770 HV0.05. The coating is composed of a primer layer and a coating main body, the coating main body is connected with the substrate through the primer layer, the coating main body is sequentially and alternately composed of 2-3 different alternating layers, and the roughness Sa of the bonding surface between the primer layer and the substrate after plasma cleaning is 10-100 nm. The Vickers indentation of the coating under 10 kgf has no radial crack, the L c3 >50N in the scratch method, and the coating around the HRC indentation under 150 kgf in the indentation method has no peeling and radial crack. Compared with the prior art, the pure alpha-Ta coating with adjustable performance can be obtained at low temperature (less than 250 DEG C), without expensive gas (only argon is used), without post-heat treatment and without heterogenous metal primer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of physical vapor deposition, specifically to a high-load-bearing, high-adhesion pure α-Ta coating and its preparation method. Technical Background

[0002] Bulk tantalum (Ta) metal possesses excellent physical and chemical properties: high melting point, high corrosion resistance, high ductility, and excellent biocompatibility. However, during coating preparation, researchers have discovered that a significant proportion of β-Ta appears under typical deposition conditions. Unlike typical α-Ta, β-Ta, due to its tetragonal structure, exhibits high hardness but also extreme brittleness. During use, it is highly prone to cracking and sudden brittle fracture. Even under the influence of internal stress within the coating, it may fragment.

[0003] Current research suggests that α-Ta can be obtained through the following methods: (1) using heavy gases such as Kr and Xe as the deposition atmosphere (which is expensive); (2) using higher temperatures, such as deposition temperatures above 375°C (CN108103463B, CN101323946A) or post-deposition heat treatment above 650°C (CN116334542A) (even at 375°C, it will have a deterioration effect on light alloys such as aluminum and magnesium and low-temperature tempered martensitic steel, such as a decrease in hardness and other properties, and may even cause temper brittleness in some steels); (3) removing the effects of adsorbed and dissolved oxygen on the substrate surface, such as first depositing a layer of Cr or Ti to isolate the substrate surface from the Ta coating (creating an additional heterogeneous interface, which may cause coating delamination or even peeling due to differences in elastic modulus or thermal expansion coefficient).

[0004] Meanwhile, current Ta coatings suffer from low adhesion (e.g., the technical solution in CN116334542A has an adhesion of only 15N).

[0005] Currently, due to the aforementioned problems, there is an urgent need to obtain a pure α-Ta coating with high adhesion and its preparation method. Summary of the Invention

[0006] Based on the above problems, this invention proposes a high load-bearing and high-adhesion pure α-Ta coating and its preparation method.

[0007] The coating has a single body-centered cubic α-phase crystal structure and a hardness of 550–770 HV0.05.

[0008] The coating consists of two parts: a base layer and a main coating layer. The main coating layer is connected to the substrate through the base layer. The grain size of the base layer is smaller than that of the main coating layer. The main coating layer is composed of 2 to 3 different alternating layers in sequence. The interface between the base layer and the substrate has surface bumps and depressions with a roughness Sa of 10 to 100 nm. The surface bumps and depressions are generated in situ during the deposition process, and the surface bumps and depressions of the interface are isotropic.

[0009] The isotropic surface bumps and depressions of the bonding surface ensure that the bonding force between the coating and the substrate remains consistent in any direction, while maximizing the specific surface area of ​​the surface.

[0010] The coating's high load-bearing capacity is demonstrated by the fact that the coating exhibits no radial cracks under Vickers indentation at 10 kgf.

[0011] The high adhesion of the coating is reflected in: L in the scratch test c3 >50N, in the indentation method at 150kgf, the coating around the HRC indentation showed no peeling or radial cracks.

[0012] Preferably, the coating body is composed of alternating layers arranged in sequence as an alternating group, and the number of alternating groups of the coating body is not less than 3 groups; the thickness of any alternating layer is 100-1000 nm; the thickness of the underlayer is 100-500 nm; and the thickness of the underlayer is not greater than 1 / 10 of the thickness of the coating body.

[0013] Preferably, the different alternating layers differ in any one or a combination of hardness, elastic modulus, density, and coefficient of thermal expansion.

[0014] The superposition of multiple layers with different properties allows for synergistic effects between different layers. For example, alternating coatings with varying hardness can combine strength and toughness; the lower-hardness layer can absorb more energy through plastic deformation, delaying coating failure, while the higher-hardness layer provides better support. Different densities allow for a variable combination of strength, conductivity, and corrosion resistance in the coating. Compared to single-layer coatings, alternating coatings help to prevent the inevitable development of defects during the deposition process into through-hole defects (through interfaces, vias, etc.), resulting in better corrosion resistance and density.

[0015] Preferably, the surface texture and depressions at the interface between the underlayer and the substrate are generated in situ by plasma cleaning during the coating preparation process.

[0016] The surface texture and depressions of the bonding surface can provide a larger contact area, forming more metallic bonds between the coating and the substrate, thus enhancing the adhesion. Simultaneously, when subjected to an external force with a horizontal component, it can reduce the pressure on the film-substrate cross-section in that direction. However, excessive undulation may lead to porosity during coating deposition due to the shadowing effect; insufficient undulation will not provide adequate single-point strength, making single points prone to yielding during use.

[0017] Furthermore, the surface bumps and depressions are generated in situ by plasma cleaning during the coating preparation process, which can ensure that there will be no secondary contamination in additional steps and environments (doping with trace elements, such as the addition of trace amounts of oxygen, may lead to changes in the crystal structure, thereby degrading performance) or additional processes.

[0018] The method for preparing a high-load-bearing, high-adhesion pure α-Ta coating as described above is characterized by comprising the following steps:

[0019] S1. Cleaning: The substrate material is plasma cleaned using AEGD technology to ensure the required surface roughness and remove oxide films or contaminants from the sample surface.

[0020] S2. Underlayer deposition: The underlayer is prepared using high-power pulsed magnetron sputtering (HiPIMS) technology combined with direct-current magnetron sputtering (DCMS) technology and a tantalum target with a purity greater than 99.95 wt%. The deposition atmosphere pressure is 0.3 to 0.6 Pa.

[0021] S3, Coating substrate deposition: The coating substrate was prepared using HiPIMS superimposed DCMS technology and a tantalum target with a purity greater than 99.95 wt%, with a bias voltage less than S2 and a deposition atmosphere pressure of 0.3–0.6 Pa;

[0022] In S3, different alternating layers can be obtained by adjusting any one or a combination of bias voltage, duty cycle, target power, and DCMS / HiPIMS ratio;

[0023] The target-substrate distance is 80–100 mm.

[0024] The entire environment was filled with argon.

[0025] AEGD technology, or Arc Enhanced Glow Discharge, generates ultra-high-density low-energy plasma. Combined with pulsed bias technology, it enables efficient and rapid cleaning with lower temperature rise and less surface damage. Simultaneously, it allows for controllable in-situ fabrication of sawtooth-shaped undulations. Compared to traditional self-glow sputtering cleaning and high-bias metal ion cleaning, the higher-density plasma can better remove adsorbed oxygen and near-surface dissolved oxygen, while reducing surface damage and impact on surface and near-surface microstructure and properties. It also significantly reduces the likelihood of arc initiation.

[0026] An excessively small target-substrate distance may cause the substrate to enter the negative glow region. On the one hand, a small target-substrate distance will prevent the AEGD effect from being achieved; on the other hand, an excessively small target-substrate distance will cause droplets generated by the unavoidable arc on the target surface to fall directly onto the substrate surface; simultaneously, an excessively small target-substrate distance will severely affect the normal discharge of the target when a high voltage is applied to the substrate, potentially leading to quenching or arc initiation; finally, an excessively small target-substrate distance will also cause a sharp increase in the substrate surface temperature. An excessively large target-substrate distance will greatly reduce the deposition rate of the coating, resulting in a waste of Ta target and energy.

[0027] The preferred S1 temperature is no higher than 200℃, the time is 5–20 min, and the ratio of anolyte current to cathode current in AEGD is greater than 1. A temperature not exceeding 200℃ effectively avoids the first type of temper brittleness in most steels, and is also more favorable to light alloys, preventing alloying element re-dissolution or large-scale dislocation migration and annihilation, thus avoiding impact on their mechanical properties. The ratio of anolyte current to cathode current ensures that elements in the cathode target do not leak, preventing contamination of the matrix. Simultaneously, it generates a sufficiently dense low-energy plasma.

[0028] Preferably, in S2, the current ratio of DCMS / HiPIMS is not greater than 1, the temperature is not higher than 200℃, the bias voltage is 400~600V, and the target peak power density is not less than 1800W / cm². 2 A current ratio of no more than 1 for DCMS / HiPIMS ensures that β-Ta is not formed. The high-energy particles of HiPIMS can activate the sputtered atoms generated by DCMS, increasing their energy. A higher bias voltage allows ions to maintain sufficient energy when bombarding the substrate surface, achieving "pseudo-implantation" while further removing any residual impurities on the surface. Simultaneously, the higher energy ensures the formation of pure α-Ta. Insufficiently low target peak power density may reduce ionization, failing to fully utilize the HiPIMS technology, leading to insufficient deposition rate or insufficient total particle quantity, and consequently, insufficient coating energy to form β-Ta.

[0029] Preferably, in S3, the current ratio of DCMS / HiPIMS is not greater than 1, the temperature is not higher than 250℃, the bias voltage is 0~300V, and the target peak power density is not less than 1500W / cm². 2 During the deposition of the main coating, the coating body does not directly contact the substrate due to the presence of the underlayer. At this time, a lower bias voltage and target power can be used to "inherit" the crystal structure of the underlayer, thereby avoiding the heat accumulation caused by long-term bombardment and the crystal defects caused by high-energy bombardment.

[0030] Key technical features and beneficial effects of this invention:

[0031] (1) Multilayer alternating pure α-Ta design: By using a base layer of the same element as the coating to isolate the substrate from the coating body, more heterogeneous interfaces are avoided; at the same time, the base layer and the substrate surface have an in-situ raised and recessed interface, which can effectively enhance the film-substrate bonding force; the multilayer alternating design of the coating body with different properties can realize the control of coatings with different properties.

[0032] (2) Design of AEGD coupled DCMS / HiPIMS: The substrate surface is cleaned by ultra-high density low-energy plasma to fully remove oxygen. At the same time, a high bias voltage is used to lay the underlayer to further remove any possible trace residual oxygen and establish an "isolation layer" between the coating body and the substrate. Multiple constraints on the target-substrate distance and the target peak power density ensure that the underlayer is pure α-Ta, laying the foundation for obtaining pure α-Ta through low-energy deposition of the coating body. The deposition temperatures all avoid the first type of temper brittleness of steel and the solid solution temperature range of light alloys, so as not to have a significant impact on the mechanical properties, crystal structure and elemental distribution of the substrate. Attached Figure Description

[0033] Figure 1 XRD pattern of Example 1;

[0034] Figure 2 Example 1: Coating cross-sectional view;

[0035] Figure 3 HRC indentation diagram at 150 kgf in Example 1;

[0036] Figure 4 Example 1: 10 kgf Vickers indentation;

[0037] Figure 5 HRC indentation diagram at 150 kgf in Example 2;

[0038] Figure 6 Example 2: 10 kgf Vickers indentation;

[0039] Figure 7 Example 2: Polarization curve;

[0040] Figure 8 HRC indentation diagram at 150 kgf for Comparative Example 1. Detailed Implementation

[0041] The implementation method is described in detail below with reference to the accompanying drawings and embodiments:

[0042] Example 1

[0043] The substrate used in this embodiment is 20Cr13, with a final heat treatment temperature of 300℃ and a hardness of 450HV0.05.

[0044] S1. Cleaning: The substrate material is plasma cleaned using AEGD technology; temperature 200℃, time 15min, anodic current and cathode current in AEGD are 90A and 70A respectively.

[0045] S2. Underlayer Deposition: The underlayer was prepared using HiPIMS superimposed DCMS technology and a tantalum target with a purity greater than 99.95 wt%. The deposition atmosphere pressure was 0.5 Pa; the DCMS / HiPIMS current ratio was 0.75, the temperature was 200℃, the bias voltage was 500 V, and the target peak power density was 2500 W / cm³. 2 ;

[0046] S3. Coating substrate deposition: The coating substrate was prepared using HiPIMS superimposed DCMS technology and a tantalum target with a purity greater than 99.95 wt%. The deposition atmosphere pressure was 0.5 Pa; the DCMS / HiPIMS current ratio was 0.75; the temperature was 200℃; the bias voltage was alternating between 50 and 250 V; and the target peak power density was 2400 W / cm³. 2 ;

[0047] The target distance is 90 mm.

[0048] The obtained coating crystal structure is as follows Figure 1 As shown, this is the α phase of a pure body-centered cubic lattice.

[0049] According to GB / T 4340.1-2009 "Metallic materials Vickers hardness test - Part 1: Test method", the coating hardness is 655 HV0.05, and the substrate hardness after deposition is 445 HV0.05.

[0050] like Figure 2 As shown, the coating consists of two parts: a base layer and a main coating layer. The main coating layer is connected to the substrate through the base layer. The grain size of the base layer is smaller than that of the main coating layer. The main coating layer is composed of two alternating layers with different hardnesses, with a total of 9 alternating groups.

[0051] The base coat is 400nm thick; the alternating layers of the main coating are 1000nm thick.

[0052] The surface roughness of the sample after S1 was characterized by AFM technology, Sa = 20 nm.

[0053] The surface bumps and depressions of the mating surfaces are isotropic.

[0054] like Figure 3 and Figure 4 As shown, at Lc3 = 55 N and 150 kgf, the coating around the HRC indentation showed no peeling or cracking (according to VDI 3198 standard, better than HF 1), and the coating showed no radial cracks at 10 kgf Vickers indentation.

[0055] In additional experiments, we prepared pure Ta coatings deposited using bias voltages of 250 and 50V, respectively, with hardnesses of 585HV and 725HV.

[0056] Example 2

[0057] The difference from Example 1 is as follows:

[0058] The substrate used in this embodiment is titanium particle reinforced magnesium matrix composite material (AZ91 / 12.5wt%Ti), in the extruded state, with a hardness of 80HV0.05.

[0059] S1. Cleaning: Temperature 120℃, Time 10min.

[0060] S2. Sub-base deposition: Deposition atmosphere pressure 0.4 Pa, temperature 150℃, bias voltage 500 V, target peak power density 2200 W / cm³ 2 ;

[0061] S3. Underlying layer deposition: Deposition atmosphere pressure 0.4 Pa, temperature 120℃, alternating bias voltages of 100V and 50V to obtain alternating layers, target peak power density 2100W / cm³. 2 .

[0062] The target distance was 95mm throughout the entire process.

[0063] The thickness of the base layer is 500nm; the thickness of the alternating layer is 500nm, and the number of alternating groups is 15.

[0064] The adhesion of the coating was evaluated using the scratch test, with Lc3 = 57 N.

[0065] like Figure 5 and Figure 6 As shown, the coating around the HRC indentation at 150 kgf showed no peeling or cracking (according to VDI 3198 standard, better than HF 1), and the coating showed no radial cracks at 10 kgf Vickers indentation.

[0066] According to GB / T 4340.1-2009 "Metallic materials Vickers hardness test - Part 1: Test method", the hardness of the coating is 685HV0.05, and the hardness of the substrate after deposition is 82HV0.05.

[0067] The surface roughness of the sample after S1 was characterized by AFM technology, Sa = 17 nm.

[0068] In additional experiments, we prepared pure Ta coatings deposited using bias voltages of 100 and 50V, respectively, with hardnesses of 630 HV and 725 HV.

[0069] like Figure 7 As shown, electrochemical tests were performed using a Versa STAT 3F, and the self-corrosion current density was 2.7 × 10⁻⁶. -8 A / cm 2 Compared to titanium particle magnesium matrix materials, the corrosion resistance is reduced by 5 orders of magnitude, resulting in a significant improvement.

[0070] Example 3

[0071] The difference from Example 2 is that:

[0072] The substrate used in this embodiment is an aluminum-magnesium layered composite material (6082 / AZ31 / 6082), in the extruded state, with a hardness of 150HV0.05.

[0073] S1. Cleaning: The anode current and cathode current in AEGD are 80A and 70A, respectively.

[0074] S2, Underlying deposition: Target peak power density 1800 W / cm³ 2 ;

[0075] S3. Underlying layer deposition: Bias voltage 200V, alternating duty cycles of 50% and 80% to obtain alternating layers, target peak power density 1500W / cm³. 2 .

[0076] The target distance was 100mm throughout the entire process.

[0077] The number of alternation groups is 20.

[0078] The adhesion of the coating was evaluated by the scratch test, Lc3 = 53 N, and no peeling or cracking of the coating around the HRC indentation at 150 kgf (according to VDI 3198 standard, better than HF 1), and no radial cracks in the coating at 10 kgf Vickers indentation.

[0079] The coating has a hardness of 705 HV<0.05, and the substrate hardness after deposition is 155 HV<0.05.

[0080] The surface roughness of the sample after S1 was characterized by AFM technology, Sa = 16 nm.

[0081] Alternating layers were obtained by using 50% and 80% duty cycles respectively, with the 80% alternating layer having a higher density.

[0082] Example 4

[0083] The difference from Example 1 is as follows:

[0084] The substrate used in this embodiment is TC4 with a hardness of 350HV0.05.

[0085] S3, Underlying deposition: Target peak power density 1800 / 2100 / 2400 W / cm³ 2 Obtain alternating layers.

[0086] The adhesion of the coating was evaluated by the scratch test. Lc3 = 56 N. No peeling or cracking of the coating was observed around the HRC indentation at 150 kgf (according to VDI 3198 standard, better than HF 1). No radial cracks were observed in the 10 kgf Vickers indentation of the coating.

[0087] The coating has a hardness of 665 HV<0.05, and the substrate hardness after deposition is 350 HV<0.05.

[0088] As the peak power density of the target increases, the elastic modulus gradually increases, reaching 235 / 250 / 260 GPa respectively through nanoindentation tests on the additionally prepared single-layer coating.

[0089] Example 5

[0090] The difference from Example 1 is as follows:

[0091] The substrate used in this embodiment is MPS 700 (Cr-Ni-Mo-V steel), with a final heat treatment temperature of 600℃ and a hardness of 505HV0.05.

[0092] The number of alternating groups is 12;

[0093] The thickness of the substrate is 500nm;

[0094] The thickness of any alternating layer of the coating body is 800 nm;

[0095] The adhesion of the coating was evaluated by the scratch test. Lc3 = 60 N. At 150 kgf, there was no peeling or cracking of the coating around the HRC indentation (according to VDI 3198 standard, better than HF 1). There were no radial cracks in the 10 kgf Vickers indentation of the coating.

[0096] According to GB / T 4340.1-2009 "Metallic materials - Vickers hardness test - Part 1: Test method", the hardness of the coating is 727 HV0.05, and the hardness of the substrate after deposition is 510 HV0.05.

[0097] The surface roughness of the sample after S1 was characterized by AFM technology, Sa = 40 nm.

[0098] Comparative Example 1

[0099] To further demonstrate the beneficial effects of the proposed solution, the inventors have provided typical comparative examples here.

[0100] The difference from Example 1 is as follows:

[0101] S3. Coating deposition: Bias voltage 50V without alternation, coating thickness is consistent with Example 1;

[0102] The obtained coating crystal structure is a single body-centered cubic α phase.

[0103] like Figure 8 Radial cracks appeared in the coating around the HRC indentation at 150 kgf. According to the VDI 3198 standard, it can be rated as HF1 to 2, which has worse adhesion and load-bearing capacity than all the aforementioned embodiments.

Claims

1. A high-load-bearing, high-adhesion pure α-Ta coating, characterized in that, The coating has a single body-centered cubic α-phase crystal structure and a hardness of 550–770 HV0.

05. The coating consists of two parts: a base layer and a main coating layer. The main coating layer is connected to the substrate through the base layer. The grain size of the base layer is smaller than that of the main coating layer. The main coating layer is composed of 2 to 3 different alternating layers in sequence. The bonding surface between the base layer and the substrate has surface relief and depression, with a roughness Sa of 10 to 100 nm. The surface protrusions and depressions of the mating surface are isotropic; The coating’s high load-bearing capacity is demonstrated by the fact that the coating showed no radial cracks under Vickers indentation at 10 kgf. The high adhesion of the coating is reflected in: L in the scratch test c3 >50 N, in the indentation method at 150 kgf, the coating around the HRC indentation showed no peeling or radial cracks; The coating body is composed of alternating layers arranged in sequence to form an alternating group, and the number of alternating groups of the coating body is not less than 3 groups; the thickness of any alternating layer is 100 to 1000 nm. The thickness of the substrate layer is 100–500 nm; The thickness of the undercoat layer is no more than 1 / 10 of the thickness of the main coating layer; The different alternating layers differ in any one or a combination of hardness, elastic modulus, density, and coefficient of thermal expansion.

2. The high load-bearing and high-adhesion pure α-Ta coating according to claim 1, characterized in that, The surface unevenness and depressions at the interface between the underlayer and the substrate are generated in situ through plasma cleaning during the coating preparation process.

3. A method for preparing a high-load-bearing, high-adhesion pure α-Ta coating according to any one of claims 1 to 2, characterized in that, It includes the following steps: S1. Cleaning: Plasma cleaning of the substrate material is performed using AEGD technology; S2. Underlayer deposition: The underlayer was prepared using HiPIMS superimposed DCMS technology and a tantalum target with a purity greater than 99.95 wt%, with a deposition atmosphere pressure of 0.3–0.6 Pa. S3, Coating substrate deposition: The coating substrate was prepared using HiPIMS superimposed DCMS technology and a tantalum target with a purity greater than 99.95 wt%, with a bias voltage less than S2 and a deposition atmosphere pressure of 0.3–0.6 Pa; In S3, different alternating layers can be obtained by adjusting any one or a combination of bias voltage, duty cycle, target power, and DCMS / HiPIMS ratio; The target-substrate distance is 80–100 mm.

4. The method for preparing a high-load-bearing, high-adhesion pure α-Ta coating according to claim 3, characterized in that, The temperature of S1 is not higher than 200 ℃, the time is 5 to 20 min, and the ratio of anode current to cathode current in AEGD is greater than 1.

5. The method for preparing a high-load-bearing, high-adhesion pure α-Ta coating according to claim 3, characterized in that, In S2, the current ratio of DCMS / HiPIMS is no greater than 1, the temperature is no higher than 200 ℃, the bias voltage is 400~600 V, and the target peak power density is no less than 1800 W / cm². 2 .

6. The method for preparing a high-load-bearing, high-adhesion pure α-Ta coating according to claim 3, characterized in that, In S3, the current ratio of DCMS / HiPIMS is no greater than 1, the temperature is no higher than 250 ℃, the bias voltage is 0~300 V, and the target peak power density is no less than 1500 W / cm². 2 .

Citation Information

Patent Citations

  • Preparation of nanocrystalline metal Ta film having out phase structure

    CN101323946A

  • A method for preparing a body-centered cubic tantalum coating

    CN108103463B

  • Orthopedic implant plated with tantalum plating layer on surface and preparation method thereof

    CN116334542A

  • High-toughness nano-composite coating containing multi-layer structure and preparation method of high-toughness nano-composite coating

    CN115125486A